HUBUNGAN LINGKUNGAN SOSIAL KELUARGA DENGAN DAYA JUANG MAHASISWA PPKN FKIP UNILA DALAM PENYELESAIAN TUGAS AKHIR - Herbiyansa Putra Pratama; Devi Sutrisno Putri; Yunisca Nurmalisa; Nurhayati; Mohammad Mona Adha (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study was motivated by the fact that some students of the Civic Education (PPKn) Study Program at the Faculty of Teacher Training and Education, University of Lampung, still experience difficulties in maintaining consistency and perseverance (adversity quotient) while completing their thesis. One external factor presumed to play an important role is the family social environment, which includes emotional, instrumental, informational, and appraisal support. This research aimed to determine whether there is a relationship between the family social environment and students’ adversity quotient in completing their thesis. The study employed a quantitative method with a correlational approach. The population consisted of 116 PPKn students from the 2022 cohort who were in the process of writing their thesis, with a sample of 90 students determined using the Taro Yamane formula and random sampling technique. The research instrument was a questionnaire developed based on indicators of the family social environment and the adversity quotient indicators (control, ownership, reach, and endurance). Data were analyzed using SPSS through correlation tests, normality tests, linearity tests, and hypothesis testing. The results showed a strong and positive relationship between the family social environment and students’ adversity quotient. These findings indicate that the better the family social support, the higher the students’ adversity quotient in completing their thesis. This study provides empirical evidence that strengthening the role of the family is a strategic factor in enhancing students’ resilience, perseverance, and ability to overcome academic challenges.